2017
DOI: 10.14414/jebav.v19i3.517
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effects of Role Overload and Role Conflict on Performance through Job Stress as a Mediating Variable in the Cellular Phone Trading Centers in Surabaya

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…This is consistent with the findings of previous studies investigated by (Rusinta et al, 2019) where job stress mediates the effect of multiple role conflicts on employee performance in the Department of Revenue Financial and Asset Management, Kulon Progo Regency. Similar results are also found by (Sutanto & Wiyono, 2017) job stress has a significant effect as a mediating role of multiple role conflicts on performance. Based on the description above, the proposed hypothesis 4 (H4) is multiple roles conflict affects the performance of female employees through job stress mediation variables…”
Section: Literature Reviewsupporting
confidence: 85%
“…This is consistent with the findings of previous studies investigated by (Rusinta et al, 2019) where job stress mediates the effect of multiple role conflicts on employee performance in the Department of Revenue Financial and Asset Management, Kulon Progo Regency. Similar results are also found by (Sutanto & Wiyono, 2017) job stress has a significant effect as a mediating role of multiple role conflicts on performance. Based on the description above, the proposed hypothesis 4 (H4) is multiple roles conflict affects the performance of female employees through job stress mediation variables…”
Section: Literature Reviewsupporting
confidence: 85%
“…The literature reports ample evidence that employee performance is affected by role conflicts [1], [7], [8], [18], [19], [5]. The findings uncovered that role conflict negatively influenced employee performance.…”
Section: Employee Performancementioning
confidence: 99%
“…When employees feel pressured or burdened while completing their work, their performance will be impaired. The empirical research results revealed that increasing job stress would reduce one's job, and conversely, when job stress decreased, it would improve one's performance [2], [3], [4], [5], [6]. Based on these empirical instructions, the following hypothesis was proposed: H2: Job stress negatively and significantly affects employee performance.…”
Section: Job Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The role overloads and role conflicts among the workers steered to job stress, in that way, impacting their job performance. Job stress and role overloads and conflict share a positive relationship, while job stress and job performance share a negative relationship (Sutanto & Wiyono, 2017). Moreover, role conflict hurts the organizational commitment with the mediating factor of high job involvement factor compared to moderate or low job involvement.…”
Section: Review Of Literaturementioning
confidence: 99%